Diagnostic accuracy of a non-invasive spot-check hemoglobin meter, Masimo Rad-67® pulse CO-Oximeter®, in detection of anemia in antenatal care settings in Kenya - Angela Koech; Angela Koech; Angela Koech; Isaac Mwaniki; Joseph Mutunga; Moses Mukhanya; Emily Mwadime; Marvine Ochieng; Grace Mwashigadi; Hiten D. Mistry; Rachel Craik; Peter von Dadelszen; et al. (Frontiers Media S.A., 2024)
BackgroundPoint of care hemoglobin meters play key roles in increasing access to anemia screening in antenatal care especially in settings with limited access to laboratories. We aimed to determine the diagnostic accuracy of a non-invasive spot-check hemoglobin (SpHb) meter, Masimo Rad-67® Pulse CO-Oximeter®, in the diagnosis of anemia in pregnant women attending antenatal care clinics in Kilifi, Kenya.MethodsThis was a diagnostic accuracy study that retrospectively evaluated SpHb against a validated reference standard of laboratory assessed hemoglobin (Lab Hb) by a SYSMEX XN-330 automated hematology analyzer. The study was nested within a prospective pregnancy cohort study that recruited unselected pregnant women from antenatal care clinics in two public hospitals in Kilifi County, coastal Kenya. Records with both SpHb and Lab Hb were selected from pregnancy visits between May 2021 and December 2022. Linear regression and Bland-Altman analysis were performed to compare the two tests and diagnostic accuracy parameters obtained for the diagnosis of anemia.ResultsA total of 2,975 records (from 2,203 unique participants), with paired SpHb and Lab Hb were analyzed. Linear regression showed a significant but weak positive correlation, a proportional bias of 0.44 (95% CI 0.41-0.47) and a constant of 7.59 (95% CI 7.30-7.87, p < 0.001). The median bias was 1.70 g/dl, with limits of agreement of −0.80 to 4.20. SpHb tended to be higher than Lab Hb on the low hemoglobin range but lower than Lab Hb on the high hemoglobin range. The sensitivity of SpHb in detecting anemia was 18.66%. Prevalence, specificity, positive predictive value, and negative predictive values were 46.37%, 96.77%, 83.33%, and 57.92% respectively.ConclusionOverall, SpHb by Masimo Rad-67® Pulse CO-Oximeter® did not accurately identify pregnant women with anemia and many cases would be missed. We would not recommend its use in antenatal care settings.